Latent Thermal Energy Storage Application in a Residential Building at a Mediterranean Climate - Luis Coelho; Maria K. Koukou; George Dogkas; John Konstantaras; Michail Gr. Vrachopoulos; Amandio Rebola; Anastasia Benou; John Choropanitis; Constantine Karytsas; Constantinos Sourkounis; Zenon Chrysanthou (Energies, 2022)
An innovative thermal energy storage system (TESSe2b) was retrofitted in a residential building in Cyprus with a typical Mediterranean climate. The system comprises flat-plate solar collectors, thermal energy storage tanks filled with organic phase change material, a geothermal installation consisting of borehole heat exchangers with and without phase change material and a ground source heat pump, an advanced self-learning control system, backup devices and several other auxiliary components. The thermal energy storage tanks cover the building’s needs at certain temperature ranges (10–17 °C for cooling, 38–45 °C for heating and 50–60 °C for domestic hot water). A performance evaluation was conducted by comparing the TESSe2b system with the existing conventional heating and cooling system. The systems were simulated using commercial software, and the performance of the systems and the building’s energy needs were calculated. Based on the energy quantities, an economic analysis followed. The equivalent annual primary energy consumption with the conventional system resulted in being 43335 kWh, while for the storage system, it was only 8398 kWh. The payback period for the storage system was calculated to be equal to 9.76 years. The operation of the installed storage system provided data for calculations of the seasonal performance factor and storage performance. The seasonal performance factor values were very high during June, July and August, since the TESSe2b system works very efficiently in cooling mode due to the very high temperatures that dominate in Cyprus. The measured stored thermal energy for cooling, heating and domestic hot water resulted in being 14.5, 21.9 and 6.2 kWh, respectively. Moreover, the total volume of the phase change material thermal energy storage tanks for heating and domestic hot water was calculated to be roughly several times smaller than the volume of a tank with water as a storage medium.